On the design of an efficient load balancing mechanism on GridSim adapted to the computing environment of heterogeneity in both resources and networks. Issue 6 (1st November 2018) - Patel, Deepak Kumar; Tripathy, Chita Ranjan
Abstract : GridSim is a widely used grid simulation tool. Since it simulates a grid environment well, it has been widely used in studies of grids. Many researchers have proposed various load‐balancing techniques in the grid, but all those cannot be used in GridSim due to the structural differences of the grid. In this study, the authors propose an enhanced load balancing method called enhanced GridSim with heterogeneity aware load balancing (EGHLB) for GridSim. The proposed algorithm EGHLB estimates system parameters such as load on the resource, the expected finish time of a Gridlet on resources on each Gridlet arrival and then balances the load by providing a new mechanism of scheduling which prevents the resource overloading and executes all the Gridlets on the heterogeneous resources within the assigned deadline. A selection method for efficient scheduling of Gridlets among heterogeneous resources is presented by taking into account the deadline, network heterogeneity, and resource heterogeneity. They simulate the proposed algorithm on the GridSim platform.